Model Komunikasi Dakwah Umar Bin Al-Khattab - Ipaenin, Sariyah (Dialogia: Jurnal Studi Islam dan Sosial, 2018)
Abstract; Due to the demand of society, Islamic Da'wah has faced complex problems. It can be observed by the spread of da'wah carried out by the Islamic priest. Shahabah were the people who continued da’wah after  the Prophet Muhammad passed away. It implied that Islam was not lost by the death of the Prophet, because he had left capable team for carrying out the teachings of Islam. One of the efforts prepared by shahabah in spreading Islam for the next generation was in the form of expanding territory in Islamic history. This mandate was then assigned to one of the Prophet's companions namely Umar bin Khattab as the descendant to his da'wah. His ability for public speaking attracts others and he was able to be a role model for the community. Da’wah must be presented communicatively and include da'wah bil hikmah hasanah. His religious lecture is at least consisting the real needs of the community, as a result,  the missionary message will attain at mad'u effectively. To reach the purpose of da'wah, it is necessary to emulate the model of the missionary message carried out by Umar bin Khattab in order to be able to optimize its  rhetoric and reality.ملخص:واجهت الدعوة الإسلامية على مر الزمن مشاكل معقدة .وتتميز هذا بانتشار الدعوة التي قام بها الداعي. بعدوفاة النبي صلى الله عليه وسلمانتقلت رسالة الدعوة إلى الصحابة. لم يمت الإسلام بموت رسول الله، لأنه قد ترك خلفًا قويًا مستعدا لتنفيذ تعاليم الإسلام قبل وفاته. تتجلى جهود الصحابة والجيل القادم على نشر الإسلام في شكل توسع ولاية في التاريخ الإسلامي. ثم أعطيت هذه المسؤولية إلى أحد صحابة الرسول، وهو عمر بن الخطاب كخليفة لوعظه. مع مهارات التواصل التي يمتلكها عمر، كان قادرا على أن يصبح نموذجًا يحتذى به للمجتمع في ذلك الوقت. يجب على داعية اليوم أن يشمل الدعوة  بالحكمة الحسنة. على الأقل محاضرته الدينية تحت عنوان الاحتياجات الحقيقية للمجتمع بحيث تصل الرسالة التبشيرية إلى المدعوين بفعالية.ولتحقيق غرض الدعوة، فإن نموذج رسالة الدعوة التي قام بها عمر بن الخطاب هو نموذج مثالي من أجل أن يكون قادراً على الاستغلال الأمثل من حيث الخطاب والواقع.Abstrak: Seiring perkembangan zaman, dakwah Islam mengalami persoalan yang kompleks. Hal ini ditandai dengan penyebaran dakwah yang dilakukan para da’i. Setelah Rasulullah SAW meninggal dunia, amanat dakwah berpindah kepada para sahabat. Islam tidak mati dengan meninggalnya Rasulullah, karena sebelum meninggal, beliau telah meninggalkan kader-kader yang tangguh yang siap mengusung ajaran Islam.Upaya para sahabat dengan generasi selanjutnya dalam menyebarkan Islam dalam bentuk perluasan wilayah dalam sejarah Islam. Amanah ini kemudian diembankan kepada salah satu sahabat Nabi yakni Umar bin Khattab sebagai penerus dakwah beliau. Dengan kecakapan komunikasi yang dimiliki Umar mampu untuk menjadi panutan terhadap masyarakat pada saat itu. Seorang komunikator dakwah pada masa kini harus mencakup dakwah bil hikmah hasanah. Model ceramah agamanya minimal bertemakan kebutuhan nyata masyarakat sehingga pesan dakwah akan sampai kepada mad’u secara efektif. Untuk mewujudkan tujuan dakwah, patut dicontohi model pesan dakwah yang dilakukan Umar bin Khattab agar mampu mengoptimilkan dari segi retorika dan realita.